COVID‐19 and transplantation—Data censoring. Issue 8 (28th April 2022) - Subramanian, Vijay; Anderson, Christopher; Karp, Seth; Pastan, Stephen; Gerber, David; Locke, Jayme; Cohen, Ari; Shah, Malay; Casingal, Vincent; Strata, Robert; Singh, Neeraj; DuBay, Derek; et al.
Abstract : During the early wave of the COVID‐19 pandemic, the Scientific Registry of Transplant Recipients (SRTR) designated a "black out" period between March 12, 2020, and June 12, 2020, for transplant outcomes reporting. We discuss the implications and potential bias it has introduced as it may selectively favor the outcomes for certain regions and harm other regions due to varied effects of different waves of COVID‐19 infections across the United States. Abstract : The differential regional impact of COVID‐19 during its early wave may translate into a differential impact of data censoring on transplant centers.